Influence Leadership Principal and Teacher Certification Teacher Performance Against SMA Ekasakti Padang - M.Pd, Detman (RC-INSTITUT, 2018)
ABSTRACT School leadership will affect the performance of teachers, where the leadership of the breed, the principal will certainly be able to lead the high performance achieved by teachers in carrying out their daily duties. To improve the quality of education a school principal should be able to improve the performance of teachers as educators. As the head of the school leader must be able to provide effects that can cause the teacher moved to carry out its duties effectively so that their performance will be better. Teacher certification with government regulations provide certificates to teachers who already frofesional as an educator, with another katab forfesional was considered by the government in carrying out a task as educators of the nation.This type of research is the study exprimen with quantitative analysis method performed at state junior high school Ekasakti Padang. This study used a sample of 17 teachers who have received certification. Sampling technique is the total sample that is the totality of teacher certification in SMA Ekasakti Padang. School leadership impact on teacher performance SMA Ekasakti Padang. Based on the analysis of the research results prove that perbangan t with t-table of 480.89> 2.110, it suggests that the presence of school leadership influence on the performance of junior high school teacher, SMA Ekasakti Padang. Teacher certification SMA Ekasakti Padang significant effect on teacher performance SMA Ekasakti Padang. The research proves that t with t-table then the numbers obtained by 1,890,608.95> 2.110, indicating that the certification of influence on the performance of junior high school teacher, SMA Ekasakti Padang. School leadership and teacher certification SMA Ekasakti Padang jointly affect the performance of teachers SMA Ekasakti Padang. These results together can be proved by using perbangan F arithmetic with F-table then the numbers obtained by 3.20> 2.30, this indicates that the presence of the effect of school leadership and teacher certification on the performance of junior high school teachers 4 SMA Ekasakti Padang. Key Word: Leadership Principal and Teacher Certification